The role of inter- and intralingual factors and compendiums in acquisition of Swedish as a foreign language: the case of Finns learning definiteness and the use of articles - Nyqvist, Eeva-Lisa (Research in Language, 2016)
This study explores the acquisition of definiteness and article use in written Swedish by Finnish-speaking teenagers (n=67) during the three years in secondary school. The studied grammatical phenomena are problematic for all L2 learners of Swedish and are especially difficult for learners, such as Finns, whose L1 lacks expressive definiteness morphologically. The informants produce complex NPs already in their first narratives. The form of NPs poses significantly more problems than the choice of a correct form of definiteness. Hence, it is possible that previous knowledge in English helps informants in the choice of definiteness. The common nominator for problematic expressions is simplification, in both formal aspects and in the relation between form and meaning. Previous research in Sweden has made similar findings. The most central types of NPs build an acquisition explainable by a complexity hierarchy between the different types of NPs. The informants master best NPs without definiteness markers. Definite singulars containing an ending are significantly easier than indefinite singulars, the indefinite article of which is notoriously difficult for Finns learning Swedish as an L2. This acquisition order, however, profoundly differs from the traditional order of instruction of their compendiums.